Challenges and perspectives for the performance of residente social assistants graduated from the Health Residence Program comprehensive care in orthopedics and traumatology in the west of Pará (Research, Society and Development, 2022)
The article aims to identify the challenges and perspectives of professional practice of resident social workers graduated from the Multiprofessional Residency Program in Health Comprehensive Care in Orthopedics and Traumatology at the Regional Hospital of Baixo Amazonas (HRBA) in Santarém/PA. The research was guided by a critical perspective and with a qualitative approach in order to understand the object to be studied in all its aspects and connections. if a form with open and closed questions. The collected data were systematized and analyzed qualitatively based on the content analysis procedure. In the first part, there was a brief approach to the debate on Social Work and Multiprofessional Residency in health. In the second, the attributions and competences of the work of the social worker in the health policy and in the multiprofessional residency in health are approached and, finally, the main results of the research carried out within the scope of the Multiprofessional Residency Program in Health Comprehensive Care are presented. in Orthopedics and Traumatology at HRBA, such as lack of autonomy, lack of understanding of the Social Worker's professional identity, precarious working conditions and others. Furthermore, it is important to strengthen the category in the face of challenges and at the heart of Residency Programs.